Implementasi Media ETMR Board Berbasis Model Project Based Learning sebagai Upaya Peningkatan Keterampilan Menulis Permulaan - Paradisa, Fauza Cahya; Purwati, Panca Dewi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to 1) describe the implementation of ETMR Board media based on the Project Based Learning model in an effort to improve the writing skills of grade I elementary school and 2) describe the effectiveness of ETMR Board media based on the Project Based Learning model in an effort to improve the writing skills of grade I elementary school. Beginning writing is a writing skill that is taught to students in the early stages, namely in grades I and II, which is focused on: letter writing, word writing, simple sentence writing, and punctuation writing. The subjects of this study were first grade students of SD Negeri Karanganyar 01, totaling 28 students. The method used is descriptive qualitative. The data collection techniques used were interviews, observations, documentation, and tests. The results of this study indicate that the implementation of the ETMR Board based on the Project Based Learning model can 1) make it easier for students to learn the material and 2) can improve the knowledge and skills of beginning writing of first grade students of SD Negeri Karanganyar 01. This can be seen from the average results of the pretest to posttest, as much as 15.3. Thus, the number of students who are complete has also increased by 43%.